2020
DOI: 10.1007/s11012-020-01148-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the flow around a square cylinder with an upstream splitter plate at low Reynolds numbers

Abstract: The present study focuses on the flow over a 2D square cylinder, with a plate placed in front of it. An inhouse code using the lattice Boltzmann method (LBM) was employed for all the simulations presented. Few cases were simulated using the open source code Nektar++, the results obtained from both methodologies were compared. Regarding the plate, three related parameters, velocity ratio, distance between the plate and cylinder, and the thickness of the plate, were studied in order to evaluate the impact of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In the present manuscript, we have chosen to place the square cylinder in a thin shear layer created by a piecewise-constant velocity profile with the discontinuity separating the top and bottom homogeneous streamwise velocities precisely located at cylinder mid-height. The same configuration was previously used by Mushyam and Bergada 60 , An et al 61 , although the flow was intentionally kept two-dimensional. This kind of upstream conditions may be obtained experimentally in a wind or water tunnel 62 , and the development of the shear layers thus generated have been thoroughly investigated [63][64][65] .…”
Section: Introductionmentioning
confidence: 99%
“…In the present manuscript, we have chosen to place the square cylinder in a thin shear layer created by a piecewise-constant velocity profile with the discontinuity separating the top and bottom homogeneous streamwise velocities precisely located at cylinder mid-height. The same configuration was previously used by Mushyam and Bergada 60 , An et al 61 , although the flow was intentionally kept two-dimensional. This kind of upstream conditions may be obtained experimentally in a wind or water tunnel 62 , and the development of the shear layers thus generated have been thoroughly investigated [63][64][65] .…”
Section: Introductionmentioning
confidence: 99%
“…Here we choose to submerge the square cylinder in a thin shear layer by replacing the classic upstream homogeneous shear by a piecewise-constant velocity profile with the discontinuity separating the top and bottom homogeneous streamwise velocities precisely located at cylinder mid-height. This same set-up has been used twice before, but the flow was expressly kept two dimensional (Mushyam & Bergada 2017;An et al 2020). In order to simulate experimentally reproducible conditions, we choose to separate the top and bottom homogeneous velocity streams by a flat plate, such that the shear layer results from the reunion, at its trailing edge, of the top and bottom boundary layers and develops smoothly downstream before reaching the cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…The geometric shape of the cylinder strongly influences the wake behind a cylinder on the hydrodynamic forces. Several articles and scientific research papers based on the study of this physical phenomenon and the importance of the problem have been found [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%